2011
DOI: 10.1029/2009gb003615
|View full text |Cite
|
Sign up to set email alerts
|

Can N2O stable isotopes and isotopomers be useful tools to characterize sources and microbial pathways of N2O production and consumption in tropical soils?

Abstract: Nitrous oxide (N2O) is an important greenhouse gas in which the main sources are tropical rainforest and agricultural soils. N2O is produced in soils by microbial processes, which are enhanced by the application of nitrogenous fertilizers. The soil N2O bulk isotopic composition (δ15Nbulk and δ18O) and the “site‐specific,” or intramolecular, 15N isotopic composition, i.e., the 15N/14N ratio at the cenral (α) or terminal (β) nitrogen position, expressed in this study as δ15Nα and δ15Nβ could help identify both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
133
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(154 citation statements)
references
References 60 publications
17
133
1
1
Order By: Relevance
“…However, the latest IPCC Assessment Report (Ciais et al, 2013) for the first time separated oceanic emissions into a natural component and an anthropogenic component, e.g., due to atmospheric N deposition to rivers (Syakila and Kroeze, 2011;Duce et al, 2008;Kroeze et al, 2005). The oceanic fraction of the anthropogenic source was estimated as 1 Tg year −1 N. N 2 O emitted from agricultural soils and biomass burning is more depleted in δ 15 N av and δ 18 O than the tropospheric background (Park et al, 2011;Goldberg et al, 2010;Ostrom et al, 2010;Tilsner et al, 2003;Pérez et al, 2001Pérez et al, , 2000, while N 2 O emitted from other minor sources, such as automobiles, coal combustion, and industry, has values closer to tropospheric N 2 O values (Syakila and Kroeze, 2011;Toyoda et al, 2008;Ogawa and Yoshida, 2005a, b). An increase in strongly depleted agricultural emissions in the first part of our reconstruction, followed by a decreasing relative contribution from agriculture and increasing contributions from more enriched sources like industry, automobiles, and coal combustion, could qualitatively explain the reconstructed changes in isotope signatures of both the total source and the anthropogenic component.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latest IPCC Assessment Report (Ciais et al, 2013) for the first time separated oceanic emissions into a natural component and an anthropogenic component, e.g., due to atmospheric N deposition to rivers (Syakila and Kroeze, 2011;Duce et al, 2008;Kroeze et al, 2005). The oceanic fraction of the anthropogenic source was estimated as 1 Tg year −1 N. N 2 O emitted from agricultural soils and biomass burning is more depleted in δ 15 N av and δ 18 O than the tropospheric background (Park et al, 2011;Goldberg et al, 2010;Ostrom et al, 2010;Tilsner et al, 2003;Pérez et al, 2001Pérez et al, , 2000, while N 2 O emitted from other minor sources, such as automobiles, coal combustion, and industry, has values closer to tropospheric N 2 O values (Syakila and Kroeze, 2011;Toyoda et al, 2008;Ogawa and Yoshida, 2005a, b). An increase in strongly depleted agricultural emissions in the first part of our reconstruction, followed by a decreasing relative contribution from agriculture and increasing contributions from more enriched sources like industry, automobiles, and coal combustion, could qualitatively explain the reconstructed changes in isotope signatures of both the total source and the anthropogenic component.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using pure AOB cultures have indicated that a positive SP (30-38%) is consistent with a N 2 O source from hydroxylamine oxidation (ammonia oxidation), whereas nitrifier denitrification (and denitrification) is thought to produce N 2 O with a SP value near or below zero (-10 to 0%) (Frame and Casciotti, 2010;Sutka et al, 2006). The N 2 O emissions from various soils have positive (0-35%) SP signatures (Pérez et al, 2001;Park et al, 2011Park et al, , 2012Toyoda et al, 2011), which indicates that ammonia oxidation is an important source of soil N 2 O. The SP values of soil AOA strains (MY1-3 and JG1) were distinct and they ranged from 20 to -30%, except strain CS (Table 2).…”
Section: Aoa Strainsmentioning
confidence: 99%
“…However, occasionally (e.g., D-O event 15 and 17) the N 2 O concentration increases long before the onset of the dramatic temperature change (Schilt et al, 2010), providing a potential early warning for rapid climate change. Isotopomers of N 2 O provide information on the sources (Pérez et al, 2000(Pérez et al, , 2001Park et al, 2011), i.e., whether N 2 O originates predominately from nitrification or denitrification processes. As the conditions/circumstances leading to emissions from the two processes differ both for the marine and terrestrial sources, measuring isotopomers potentially improves our understanding of the climate conditions leading to the release of N 2 O over rapid climatic changes.…”
Section: Introductionmentioning
confidence: 99%